2017
DOI: 10.3390/ijerph14090987
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Distribution Characteristics of Salivary Cortisol and Immunoglobulin A Concentrations

Abstract: Salivary cortisol and secretory immunoglobulin A (S-IgA) are important biomarkers for environmental and public health research. The present study investigated the diurnal variations of these salivary biomarkers, with a focus on the change of distribution characteristics (i.e., skewness and kurtosis) of the concentrations. The participants in this study were 113 healthy young males. Salivary samples were collected in the morning (6:30–7:30 a.m.) and afternoon (1:00–4:00 p.m.). The skewness and kurtosis of saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
3
14
1
4
Order By: Relevance
“…The simple main effect was then analyzed as a post-hoc test. The above statistical tests were performed on natural-logtransformed data rather than raw cortisol concentrations because cortisol concentrations exhibit a non-normal distribution except in the early morning (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…The simple main effect was then analyzed as a post-hoc test. The above statistical tests were performed on natural-logtransformed data rather than raw cortisol concentrations because cortisol concentrations exhibit a non-normal distribution except in the early morning (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Salivary cortisol concentration indicated a significant decrease in forest environments compared with that in urban environments, accompanying a more skewed and kurtotic distribution ( 10 ). This modification of the distribution curve might be attributed to a floor effect ( 28 , 29 ). Therefore, an unchanged distribution curve is a specific response in log-transformed HRV indicators.…”
Section: Discussionmentioning
confidence: 98%
“…When using these salivary biomarkers in research, time of collection needs to be standardized. Even though it has been shown that sIgA displays diurnal variation [8, 16, 17, 19, 43], it is not always taken into account in other studies [6, 7, 30, 44]. Thus, the diurnal pattern of sIgA is not yet widely accepted and accounted for in all research areas.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sIgA has been utilized as a marker for mucosal immunology, as a potential marker for the risk of allergy development [6, 13], and as a marker for research on sports and stress [8, 9, 1417]. It is clear from the research on mucosal immunology that the microbiota affects the development of sIgA (along with faecal IgA) [18], whereas from stress research it is known that sIgA can display diurnal rhythm [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation